2013
DOI: 10.1159/000348661
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of Pioglitazone by the Prevention of Glomerular Hyperfiltration through the Possible Restoration of Altered Macula Densa Signaling in Rats with Type 2 Diabetic Nephropathy

Abstract: Background/Aims: Pioglitazone (PGZ), one of the thiazolidinediones, has been known to show renoprotective effects. In this study, we focused on the effect of PGZ on glomerular hyperfiltration (GHF), resultant glomerular injury and altered macula densa signaling as a cause of sustained GHF through modified tubuloglomerular feedback in rats with diabetic nephropathy. Methods: Kidneys from 24-week-old male OLETF rats and LET rats, nondiabetic controls, were used for the experiment. PGZ was administered (10 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 100 publications
(70 reference statements)
2
11
0
Order By: Relevance
“…Serum creatinine and blood urea nitrogen (BUN) levels were not increased in OLETF at this age compared with the levels in LETO (Table 1). However, consistent with previous reports 27, 28 , OLETF showed higher urine albumin/creatinine and urine protein/creatinine ratios and greater kidney weight than those in LETO (Table 1). In addition, periodic acid-Schiff (PAS) staining showed that the mesangial areas tended to be increased and that the glomerular areas were significantly enlarged in OLETF compared with those in LETO (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…Serum creatinine and blood urea nitrogen (BUN) levels were not increased in OLETF at this age compared with the levels in LETO (Table 1). However, consistent with previous reports 27, 28 , OLETF showed higher urine albumin/creatinine and urine protein/creatinine ratios and greater kidney weight than those in LETO (Table 1). In addition, periodic acid-Schiff (PAS) staining showed that the mesangial areas tended to be increased and that the glomerular areas were significantly enlarged in OLETF compared with those in LETO (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…After urine collection for 24 h, blood samples were obtained from the aorta, and the rats' kidneys were perfused with ice-cold PBS (pH 7.4) and quickly removed under anesthesia (50 mg/kg ip pentobarbital) at 16, 24, and 34 wks of age (n ϭ 6). For the biochemical analysis of blood and urine samples, except Mg 2ϩ , all were measured according to published methods (3,57). Serum and urine Mg 2ϩ concentrations were measured by colorimetric tests using xylidine blue.…”
Section: Methodsmentioning
confidence: 99%
“…Sections (4 m) were prepared and stained with periodic acid-Schiff and Masson trichrome. Immunohistochemical stainings were performed as previously described (3). The other paraffin sections were treated with primary antibody, rabbit anti-TRPM6 (Osenses, Keswick, SA, Australia), diluted 1:15,000, rabbit anti-Na ϩ -Cl Ϫ cotransporter (NCC; Merck, Darmstadt, Germany), diluted 1:8,000, mouse anti-␣-smooth muscle actin (␣-SMA; Progen Biotechnik, Heidelberg, Germany), diluted 1:2,500 for 16 h at 4°C, or mouse anti-Na ϩ -Ca 2ϩ exchanger 1 (NCX1; Swant Swiss Antibodies, Marly, Switzerland) diluted 1:2,000 for 1 h at room temperature followed by Dako Cytomation EnVision plus System HRP-Labeled Polymer (Dako, Glostrup, Denmark) or Histofine Simple Stain Rat MAX PO (M) (Nichirei Biosciences, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochemical measurements of blood urea nitrogen, creatinine, sodium, and potassium were all performed as described [21]. The rats' serum and urine magnesium concentrations were measured by a colorimetric test using xylidine blue.…”
Section: Serum Biochemistrymentioning
confidence: 99%